Inflation persistence in structural macroeconomic models (RG10) - Robert-Paul Berben; Ricardo Mestre; Theodoros Mitrakos; Julian Morgan; Nikolaos G. Zonzilos (European Central Bank (ECB), 2005)
This paper analyses the response of inflation in the euro area to five macroeconomic shocks through the use of results derived from Eurosystem large-scale macroeconomic models. The main finding is that only a fiscal shock, and to a lesser extent a TFP shock, generate marked inflation persistence. In contrast, an indirect tax and an oil price shock appear much less persistent and a social security shock generates less inflation persistence in the majority of the countries (although some weak persistence was observed at the euro area level). The paper also considers evidence on the sources of persistence, which indicates that it is crucially affected by the responsiveness of wages to employment, by the sluggishness in the adjustments of the demand components, and by the speed of adjustment of employment to output and wage changes.
Keywords: C53; E31; E52; 330; impulse response function; Inflation persistence; large-scale macroeconomic models; Inflation; Schock; Makroökonometrie; Theorie; EU-Staaten; Wirkungsanalyse